Killing Cancer Discovery and Selection of New Target Molecules - Kallunki, Tuula (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Despite the efficiency of current cancer treatments, cancer is still a deadly disease for too many. In 2008, 7.6 million people died of cancer; with the current development, it is estimated that the annual cancer death number will grow to 13 million by 2030. There is clearly a need for not only more research but also more innovative and out of the mainstream scientific ideas to discover and develop even better cancer treatments. This book presents the collective works published in the recent Special Issue entitled "Killing Cancer: Discovery and Selection of New Target Molecules". These articles comprise a selection of studies, ideas, and opinions that aim to facilitate knowledge, thoughts, and discussion about which biological and molecular mechanisms in cancer we should target and how we should target them.